Analisis semiotika pidato kenegaraan terakhir Presiden Joko Widodo pada sidang tahunan MPR 2024 - Arnita, Bella; Permadi, Didi; Edy, Sarwo (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to examine the semiotic analysis of President Jokowi's final state speech at the 2024 MPR annual session through Charles Sanders Pierce's semiotic approach which involves the analysis of representamen (signs), objects (sign references), and interpretants (use of signs). This research using descriptive qualitative methods to understand the meaning and content contained in the speech. The results of the study show that "Semiotic analysis of President Jokowi's final state speech at the 2024 MPR annual session" effectively conveys emotional messages about apologies, conveying achievements, and leadership hopes. in the future. This speech teaches that whatever we do there must be something good and not good. As humans we need to be humble and apologize for what we have done so far